Recommendations to Improve the Implementation of Anemia Prevention and Control Interventions - World Bank (Washington, DC: World Bank, 2022)
The historical situation of instability in the West Bank (WB) and the Gaza Strip (GS) has multiple adverse impacts on the population. In this context, several assessments have documented a deterioration in the nutritional status of the population of the WB and GS including static or increasing prevalence of anemia, caused by iron deficiency, and other nutrition deficiencies. According to the most recent information available, anemia is a public health problem among pregnant and postnatal women, children aged 6-59 months, and adolescents. In these four groups, the prevalence of anemia is higher in the GS compared to the WB. The fact that children aged 6-59 months are affected by anemia makes it probable that children aged 0-5 months are also affected. However, this may not be reflected in the data because this age group is not normally sampled due to the procedure involved in taking a blood sample from babies. The flour fortification program aims to increase the intake of iron and other micronutrients for the whole population, by adding 10 micronutrients to wheat flour, including iron, vitamin A, and folic acid. This document provides recommendations to address demand-and-supply-side bottlenecks for wheat flour fortification and iron supplementation.